Bioprocessing for biomolecules production - Molina, Gustavo, 1983-; Gupta, Vijai Kumar, 1981-; Singh, B. N.; Gathergood, Nick, 1972- (Wiley, 2020)
"This book tackles the challenges and potential of biotechnological processes for the production of new industrial ingredients, bioactive compounds, biopolymers, energy sources, and compounds with commercial/industrial and economic interest by performing an interface between the developments achieved in the recent worldwide research and its many challenges to the upscale process until the adoption of commercial as well as industrial scale. Bioprocessing for Biomolecules Production examines the current status of the use and limitation of biotechnology in different industrial sectors, prospects for development combined with advances in technology and investment, and intellectual and technical production around worldwide research. It also covers new regulatory bodies, laws and regulations, and more. Chapters look at biological and biotechnological processes in the food, pharmaceutical, and biofuel industries; research and production of microbial PUFAs; organic acids and their potential for industry; second and third generation biofuels; the fermentative production of beta-glucan; and extremophiles for hydrolytic enzymes productions. The book also looks at bioethanol production from fruit and vegetable wastes; bioprocessing of cassava stem to bioethanol using soaking in aqueous ammonia pretreatment; bioprospecting of microbes for bio-hydrogen production; and more"--
Keywords: biomolekuly; biochemické inženýrství; biomolecules; biochemical engineering; kolektivní monografie; collective monographs